Effects of Lens-Care Solutions on Hydrogel Lens Performance. Issue 11 (November 2017) - Kitamata-Wong, Britney; Yuen, Tiffany; Li, Wing; Svitova, Tatyana; Zhou, Yixiu; Lin, Meng C.
Abstract : SIGNIFICANCE: Lens care multipurpose solutions (MPSs) can have varying effects on contact lens (CL) surface properties and the corneal epithelium. PURPOSE: The aim of this study was to investigate the short-term effects of newer MPS on CL comfort and dryness, prelens tear-film stability, and ocular-surface health. In vitro study was also performed to assess the effect of MPSs on CL surface properties. METHODS: Acuvue 2 CLs were soaked in control solution, Clear Care (CC), or test solutions: PureMoist, Biotrue, RevitaLens (RL), or saline solution (SS). Over four visits, subjects were exposed to control solution in one eye and to test solution in the contralateral eye for 2 hours using presoaked CLs. Contact lens comfort and dryness, ocular-surface health assessment, prelens noninvasive tear breakup time, and corneal epithelial permeability measured with fluorometry were assessed. Captive-sessile bubble technique evaluated CL wettability and viscous drag in vitro . RESULTS: At 10 minutes, mean comfort ± SD with PureMoist (76 ± 22) was lower than CC (86 ± 15, P = .02), Biotrue (92 ± 9, P < .005), RL (90 ± 13, P < .005), and SS (90 ± 14, P < .005). No other difference in comfort or dryness was noted. RevitaLens was associated with greater corneal epithelial permeability than CC ( P = .020) and increased corneal staining compared with all MPSs ( P < .005 for all). RevitaLens was also associated with longer prelens noninvasive tear breakup than CC ( P < .005). In vitro results agreed with clinical findings of tear-film stability as RL reduced viscous drag. Contact lens surface wettability was enhanced by all MPSs in comparison to SS. CONCLUSIONS: Differences of MPSs on the ocular surface were found in vivo and in vitro . RL caused the greatest corneal epithelium disruption but also associated with higher tear-film stability. The effect of MPSs on CL surface properties in vitro seems to reflect how MPSs altered prelens tear stability. Abstract : Supplemental digital content is available in the text.